Protection against oxidative stress-induced apoptosis in kidney epithelium by Angelica and Astragalus. (17th February 2016) - Shahzad, Muhammad; Small, David M.; Morais, Christudas; Wojcikowski, Ken; Shabbir, Arham; Gobe, Glenda C.
Abstract: Ethnopharmacological relevance: Astragalus membranaceus either alone or in combination with Angelica sinensis has been used traditionally for kidney disease in East Asia and China for thousands of years. Previous studies using in vivo animal models have shown the benefits of these medicinal herbs in kidney diseases that involve oxidative stress. However, the mechanisms by which these medicinal herbs protect kidney cells remain largely unknown. Aim of the study: To investigate the mechanisms by which ethanol, methanol and aqueous crude extracts of roots of A. membranaceus and A. sinensis afford protection to human kidney proximal tubular epithelial cells, using an in vitro model of oxidative stress. Materials and methods: Ethanol, methanol and aqueous extracts of roots of A. membranaceus and A. sinensis were prepared by a three-solvent sequential process. HK2 human kidney proximal tubular epithelial cells were treated with H2 O2 alone (0.5 mM) or in combination with different concentrations of extracts. Cell mitosis and death (microscopy) and cell viability (MTT assay) were compared. Western immunoblot was used to study expression of apoptosis-related proteins (pro-apoptotic Bax andanti-apoptotic Bcl-XL ), and cell survival (NFκB subunits p65 and p50), pro-inflammatory (TNF-α) and protective (TGFβ1) proteins. Results: H2 O2 -induced oxidative stress significantly increased apoptosis and reduced cell survival; upregulated pro-apoptotic and down-regulated Bcl-XL ; increased NFκB (p65, p50); increased TNFα and decreased TGFβ1. All changes indicated kidney damage and dysfunction. All were modulated by all extracts of both plant species, except for NFκB which was only modulated by extracts of A. membranaceus. Conclusions: In conclusion, in a model of oxidative stress that might occur after nephrotoxicity, the plant extracts were protective via anti-apoptotic and anti-inflammatory mechanisms. Graphical abstract: